New combinations for the South American Cissus striata clade (Vitaceae) - Lombardi, Julio (Phytotaxa, 2015)
Phylogenetic studies based on plastid and nuclear data (Soejima & Wen 2006, Wen et al. 2007, Ren et al. 2011, Nie et al. 2012, Rodrigues et al. 2014) have shown that Ampelopsis Michaux (1803: 159) and Cissus Linnaeus (1753: 117) (Vitaceae) are paraphyletic genera.